Effect of a ceiling fan ventilation system on finishing young bulls' health, behaviour and growth performance. (24th November 2016) - Magrin, L.; Brscic, M.; Lora, I.; Rumor, C.; Tondello, L.; Cozzi, G.; Gottardo, F.
Abstract : This research aimed at assessing the effects of a ceiling fan ventilation system on health, feeding, social behaviour and growth response of finishing young bulls fattened indoors during a mild summer season. A total of 69 Charolais young bulls were housed in six pens without any mechanical ventilation system (Control) and in six pens equipped with ceiling fans. The experimental period lasted 98 days from June until mid-September 2014. Four experimental days were considered in order to assess the effect of the ventilation system under two different microclimatic conditions: 2 alert days at monthly interval with temperature humidity index (THI) between 75 and 78, and 2 normal days with THI⩽74. Health and behaviour of the bulls were evaluated through 8-h observation sessions starting after morning feed delivery. The study was carried out during a rather cool summer with a climate average THI of 68.9 and 4 days with average THI>75. Despite these mild climate conditions, ceiling fans lowered litter moisture and acted as a preventive measure for bulls' dirtiness (odd ratio=47.9; 95% CI 19.6 to 117.4). The risk of abnormal breathing was increased for Control bulls (odd ratio=40.7; 95% CI 5.4 to 304.2). When exposed to alert THI conditions, respiration rate and panting scores increased and rumination duration dropped in Control bulls compared with bulls provided with a ceiling fan. During observations under alert THI, bulls spent less time eating, more time being inactive and consumed more water compared with normal THI conditions. Bulls' daily dry matter intake measured during the observation sessions decreased on alert compared with normal THI days ( P <0.001) due to a drop of intake during the daylight hours. Ceiling fan treatment had no effect on bulls' growth performance or water consumption but these results most likely depended on the mild climate conditions. Ceiling fans proved to mitigate some of the negative effects of heat stress on bulls' behaviour (rumination, lying down and drinking water) and respiration rate, however. The lack of a significant improvement of bulls' growth response should not discourage beef farmers from using ceiling fans in indoor systems, considering the likely increase in frequency and intensity of heat waves in the planet's temperate areas induced by global warming.